Current collector for battery, electrode for battery, method for manufacturing current collector for battery, and peeling method
A battery current collector with a primer coat layer of crystalline resin or resin-carbon mixture allows efficient peeling of the electrode active material layer, addressing the cost and contamination issues of existing methods, thereby enhancing the recycling of lithium-ion battery components.
Patent Information
- Application Number
- JP2024080296
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-06-30
- Filing Date
- 2024-05-16
- Publication Date
- 2025-01-20
AI Technical Summary
Existing methods for recovering rare metals from lithium-ion battery electrodes, such as those using ultrasonic waves, are costly and risk contaminating the processing solution with metal powder, and there is a need for a more efficient and cost-effective method to peel the electrode active material layer from the conductor layer.
A battery current collector with a conductor layer and a primer coat layer made of interspersed crystalline resin or a mixture of crystalline resin and carbon particles, where the crystalline resin has a melting point of 200°C or less, allowing the active material layer to be easily peeled off by heating the primer coat layer above its melting point.
The method reduces processing costs and contamination risks by enabling easy separation of the electrode active material layer, facilitating the recycling of valuable components.
Smart Images

Figure 2025009856000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a battery current collector, a battery electrode, and a manufacturing method and a peeling method for a battery current collector. [Background technology]
[0002] Lithium-ion batteries have excellent properties such as high energy density and long life, and are used for various purposes. The positive electrodes of lithium-ion batteries usually contain rare metals such as cobalt, nickel, and manganese, and securing these mineral resources is a challenge. Meanwhile, methods for recovering these rare metals from used lithium-ion batteries are being studied. For example, a method is known in which an electrode active material layer on a metal foil is irradiated with ultrasonic waves in a liquid tank to crush the positive electrode active material layer and remove it from the metal foil (see, for example, Patent Document 1). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2023-511520 A Summary of the Invention [Problem to be solved by the invention]
[0004] However, the ultrasonic irradiation method requires management of the treatment liquid, which increases the treatment cost, and there is a risk that the metal foil will be worn away in the treatment liquid, resulting in metal powder being mixed into the treatment liquid. The present invention has been made in view of the above circumstances, and provides a current collector for a battery that enables an electrode active material layer to be easily peeled off from a conductive layer. [Means for solving the problem]
[0005] The present invention provides a conductive layer and a primer coat layer provided on the conductive layer, the primer coat layer being a layer of scattered crystalline resin or a mixture layer of crystalline resin and carbon particles, the conductive layer being exposed in gaps between the crystalline resin contained in the primer coat layer when the primer coat layer is the layer of scattered crystalline resin, and the mass of the primer coat layer per unit area being 0.1 g / m when the primer coat layer is the mixture layer of crystalline resin and carbon particles. 2 More than 10g / m 2 and the melting point of the crystalline resin contained in the primer coat layer is 200° C. or lower. The present invention also provides a battery electrode comprising the current collector of the present invention and an electrode active material layer provided on the primer coat layer. The present invention also provides a method for producing a current collector for a battery, comprising the steps of applying a dispersion liquid in which crystalline resin particles are dispersed in a dispersion medium containing a water-soluble organic compound or a liquid organic compound and water onto a conductive layer, and drying the applied film to form a primer coat layer. The present invention also provides a method for peeling an electrode active material layer from a conductive layer, the electrode active material layer being included in an electrode comprising a current collector including a conductive layer and a primer coat layer provided on the conductive layer, and an electrode active material layer provided on the primer coat layer, the primer coat layer being a layer of a crystalline resin or a mixture layer of a crystalline resin and carbon particles, the melting point of the crystalline resin included in the primer coat layer being 200° C. or lower, and the peeling method including a peeling step of heating at least a part of the primer coat layer to a temperature equal to or higher than the melting point of the crystalline resin to peel off the electrode active material layer from the conductive layer. Effect of the Invention
[0006] By heating at least a part of the primer coating layer contained in the battery electrode using the battery current collector of the present invention to a temperature equal to or higher than its melting point, the crystalline resin can be melted and the electrode active material layer can be easily peeled off from the conductor layer, thereby reducing the cost of reusing useful components contained in the electrode active material layer and the current collector. [Brief description of the drawings]
[0007] [Figure 1] 1(a) and 1(b) are schematic cross-sectional views of a current collector for a battery according to one embodiment of the present invention. [Diagram 2] 1(a) and 1(b) are schematic cross-sectional views of a battery electrode according to one embodiment of the present invention. [Diagram 3] 1 is a SEM photograph of a cross section of a battery positive electrode after heat treatment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] Hereinafter, a number of embodiments of the present invention will be described with reference to the drawings. The configurations shown in the drawings and the following description are merely examples, and the scope of the present invention is not limited to those shown in the drawings and the following description.
[0009] First embodiment FIG. 1(a) is a schematic cross-sectional view of a battery current collector of this embodiment, and FIG. 2(a) is a schematic cross-sectional view of a battery electrode of this embodiment. The battery current collector 10 of this embodiment comprises a conductive layer 2 and a primer coating layer 3 provided on the conductive layer 2. The primer coating layer 3 is a layer of scattered crystalline resin, with the conductive layer 2 exposed in the gaps between the crystalline resin contained in the primer coating layer 3. The melting point of the crystalline resin contained in the primer coating layer 3 is 200°C or lower. The battery electrode 20 of this embodiment includes the battery current collector 10 of this embodiment and an electrode active material layer 5 provided on the primer coat layer 3.
[0010] The battery current collector 10 is a current collector for a battery electrode, and serves as a conductive path between the electrode active material layer 5 and a battery terminal. The battery is not particularly limited, but is preferably a lithium ion battery. The battery current collector 10 may be used for the positive electrode of the battery, or may be used for the negative electrode of the battery. The battery current collector 10 may be a current collector for collecting positive or negative charges from the electrode active material layer 5.
[0011] The conductive layer 2 is a main component of the battery current collector 10, and serves as a conductive path between the electrode active material layer 5 and the battery terminal. The conductive layer 2 is, for example, a metal foil, more specifically, an aluminum foil, a copper foil, a stainless steel foil, a nickel foil, or the like. The conductive layer 2 may be subjected to a corona discharge treatment before the formation of the primer coat layer 3. This can improve the hydrophilicity of the surface of the conductive layer 2, and an aqueous dispersion medium can be used in the formation of the primer coat layer 3.
[0012] The primer coating layer 3 is a layer provided on the conductor layer 2. In the battery electrode 20, the primer coating layer 3 is located between the conductor layer 2 and the electrode active material layer 5. The primer coating layer 3 functions as a binder that bonds the conductor layer 2 and the electrode active material layer 5, and can suppress peeling of the electrode active material layer 5 from the conductor layer 2 during charging and discharging of the battery.
[0013] The primer coat layer 3 is a layer of scattered crystalline resin. For example, as in the current collector 10 shown in FIG. 1(a), the primer coat layer 3 is a layer in which a plurality of crystalline resin particles 4 are scattered. Therefore, the conductive layer 2 is exposed in the gaps between the plurality of crystalline resin particles 4. By having the primer coat layer 3 having such a configuration, the conductive layer 2 and the electrode active material layer 5 can come into contact with each other in the gaps in the battery electrode 20, and the internal resistance of the battery electrode 20 can be prevented from increasing.
[0014] The crystalline resin (crystalline polymer) contained in the primer coat layer 3 is a polymer having crystallinity and has a glass transition temperature and a melting point. The melting point of the crystalline resin contained in the primer coat layer 3 is 200°C or lower. As a result, when recycling useful components contained in a used battery electrode 20, at least a part of the primer coat layer 3 is heated to a temperature equal to or higher than the melting point of the crystalline resin to melt the crystalline resin, thereby weakening the bond between the primer coat layer 3 and the conductor layer 2 or the bond between the primer coat layer 3 and the electrode active material layer 5, and the electrode active material layer 5 can be easily peeled off from the conductor layer 2. The melting point of the crystalline resin contained in the primer coat layer 3 may be 180°C or lower, or 160°C or lower.
[0015] The crystalline resin contained in the primer coating layer 3 is, for example, a polyolefin, specifically, polyethylene, polypropylene, an ethylene-propylene copolymer, etc. Furthermore, the primer coating layer 3 may contain a mixture of at least two of these resins.
[0016] The crystalline resin particles 4 contained in the primer coating layer 3 can have an average particle size D50 of 0.1 μm to 40 μm, preferably 0.1 μm to 30 μm, and more preferably 0.1 μm to 20 μm. This can prevent the internal resistance of the battery electrode 20 from increasing, and can also prevent the electrode active material layer 5 from peeling off from the conductive layer 2 during charging and discharging of the battery.
[0017] The mass of the primer coating layer 3 per unit area is, for example, 0.1 g / m 2 More than 10g / m 2 Smaller, preferably 0.3 g / m 2 More than 9g / m 2This makes it possible to prevent the internal resistance of the battery electrode 20 from increasing, and also to prevent the electrode active material layer 5 from peeling off from the conductor layer 2 during charging and discharging of the battery.
[0018] The primer coat layer 3 can be formed, for example, by applying a dispersion liquid (coating liquid) in which the crystalline resin particles 4 are dispersed in an aqueous dispersion medium onto the conductive layer 2, and drying the applied film. The method for applying the primer coat layer coating liquid onto the conductive layer 2 is not particularly limited, but may be, for example, a gravure coating method. The coating film of the coating liquid for the primer coat layer can be dried at a temperature equal to or lower than the melting point of the crystalline resin particles 4 .
[0019] The primer coat layer coating liquid (dispersion liquid) may contain a water-soluble organic compound or a liquid organic compound. This can suppress aggregation of the crystalline resin particles 4, and improve the homogeneity of the primer coat layer 3. Examples of the water-soluble organic compound or the liquid organic compound include isopropyl alcohol, dipropylene glycol monomethyl ether, diethylene glycol monomethyl ether, methylcyclohexane, ethyl acetate, N-methyl-2-pyrrolidone (NMP), cyclohexanone, tetrahydronaphthalene, and normal-dodecane. The primer coat layer coating liquid may contain two or more of these organic compounds. The proportion of the organic compound in the coating liquid for the primer coat layer is, for example, 0.5 to 85 mass percent, preferably 0.5 to 55 mass percent, and more preferably 1.0 to 35 mass percent.
[0020] The electrode active material layer 5 formed on the primer coating layer 3 may be a positive electrode active material layer or a negative electrode active material layer. The electrode active material layer 5 may have porosity and may contain electrode active material particles and a binder. In addition, the electrode active material layer 5 may contain a conductive material as necessary. The electrode active material layer 5 may be a coating film formed by applying a paste for an electrode active material layer and then drying it, or a film containing an electrode active material attached to a battery current collector 10 (for example, a battery electrode produced by a dry process, an electrode for an all-solid-state battery, etc.). In addition, in a battery electrode 20 having an electrode active material layer 5 on a battery current collector 10 having a primer coating layer formed using a primer coating layer coating liquid containing a water-soluble organic compound or a liquid organic compound, the electrode active material layer 5 has high adhesion to the battery current collector 10. In the case of a positive electrode of a lithium ion battery, the electrode active material is, for example, lithium nickel cobalt manganese oxide, lithium iron phosphate, etc. The average particle size of the electrode active material particles is, for example, 0.1 μm or more and 50 μm or less.
[0021] Second embodiment FIG. 1(b) is a schematic cross-sectional view of a battery current collector of this embodiment, and FIG. 2(b) is a schematic cross-sectional view of a battery electrode of this embodiment. The battery current collector 10 of this embodiment includes a conductive layer 2 and a primer coat layer 3 provided on the conductive layer 2. The primer coat layer 3 is a mixture layer of a crystalline resin and carbon particles. The mass of the primer coat layer 3 per unit area is 0.1 g / m. 2 More than 10g / m 2 The melting point of the crystalline resin contained in the primer coat layer 3 is smaller than that of the primer coat layer 3, and is 200° C. or lower.
[0022] The conductive layer 2 has been described in the first embodiment, and therefore will not be described here. The primer coating layer 3 is a layer provided on the conductor layer 2. In the battery electrode 20, the primer coating layer 3 is located between the conductor layer 2 and the electrode active material layer 5. The primer coat layer 3 is a mixture layer of a crystalline resin having a melting point of 200° C. or less and carbon particles. The carbon particles contained in the primer coat layer 3 serve as a conductive path between the conductor layer 2 and the electrode active material layer 5. This makes it possible to suppress an increase in electrical resistance between the conductor layer 2 and the electrode active material layer 5. The primer coat layer 3 can also have a function of protecting the conductor layer 2 from the electrolyte.
[0023] The carbon particles contained in the primer coat layer 3 are, for example, conductive materials such as graphite particles, carbon black, carbon nanotubes, graphene, etc., and mixtures of two or more of these. The average particle size D50 of the carbon particles contained in the primer coat layer 3 is, for example, 50 μm or less, preferably 30 μm or less, and more preferably 20 μm or less.
[0024] The crystalline resin (crystalline polymer) contained in the primer coat layer 3 functions as a binder for the primer coat layer 3. The crystalline resin has been described in the first embodiment, and will not be described here. The size or thickness of the crystalline resin in the primer coat layer 3 is 0.1 μm or more and 40 μm or less, preferably 0.1 μm or more and 30 μm or less, and more preferably 0.1 μm or more and 20 μm or less.
[0025] The primer coat layer 3 may contain 0.01 to 1000 parts by mass of carbon particles relative to 100 parts by mass of the crystalline resin, preferably 0.1 to 800 parts by mass of carbon particles, and more preferably 1 to 500 parts by mass of carbon particles. When the primer coat layer 3 contains carbon particles, it is possible to prevent the internal resistance of the battery electrode 20 from increasing.
[0026] The mass (weight) of the primer coat layer 3 per unit area is 0.1 g / m 2 More than 10g / m 2 or less, preferably 0.3 g / m 2 More than 7.0g / m2 or less, preferably 0.5 g / m 2 More than 5.0g / m 2 The mass of the primer coating layer 3 is 0.1 g / m 2 By setting the mass of the primer coat layer 3 at 10 g / m or more, it is possible to prevent a part of the electrode active material layer 5 from remaining on the conductive layer 2 when the electrode active material layer 5 is peeled off from the conductive layer 2 by a peeling method described later. 2 By setting it to the following, the amount of the electrode active material layer 5 in the electrode can be increased. The primer coating layer 3 may be a layer having a substantially uniform thickness.
[0027] The primer coat layer 3 may be provided so that the carbon particles contained in the primer coat layer 3 are not entirely coated with the crystalline resin. This can prevent the electrical resistance of the primer coat layer 3 from increasing. For example, a primer coat layer coating liquid, which is a mixture of an aqueous dispersion medium, carbon particles, and crystalline resin particles, is applied onto the conductor layer 2, and the coating film is dried to form such a primer coat layer 3. In other words, since the crystalline resin is almost insoluble in the aqueous dispersion medium, it is possible to prevent the carbon particles from entirely being coated with the crystalline resin. The coating method and drying of the coating film have been described in the first embodiment, and therefore will not be described here. Moreover, the electrode active material layer 5 and the electrode active material have also been explained in the first embodiment, and therefore will not be described here. The description of the first embodiment also applies to the second embodiment unless there is a contradiction.
[0028] Third embodiment The present embodiment provides a peeling method for peeling an electrode active material layer 5 included in an electrode 20 from a conductive layer 2. The peeling method of the present embodiment includes a peeling step of heating at least a part of a primer coat layer 3 included in an electrode 20 to a temperature equal to or higher than the melting point of the crystalline resin, thereby peeling the electrode active material layer 5 from the conductive layer 2.
[0029] In the peeling step, the electrode active material layer 5 may be peeled off from the conductive layer 2 in a state where the temperature of the primer coat layer 3 is equal to or higher than the melting point of the crystalline resin. Since the crystalline resin is molten in this state, the electrode active material layer 5 can be easily peeled off from the conductive layer 2. In addition, in the peeling step, at least a part of the primer coat layer 3 included in the electrode 20 may be heated to a temperature equal to or higher than the melting point of the crystalline resin (heat treatment), and then, after the temperature of the primer coat layer 3 becomes lower than the temperature of the crystalline resin, the electrode active material layer 5 may be peeled off from the conductor layer 2. In this case, the crystalline resin included in the primer coat layer 3 may be melted by the heat treatment, and the bonding strength between the primer coat layer 3 and the conductor layer 2 or the bonding strength between the primer coat layer 3 and the electrode active material layer 5 may be reduced, so that the electrode active material layer 5 may be easily peeled off from the conductor layer 2.
[0030] The peeling step may include a step of heating the electrode 20 for 0.5 to 20 seconds in a furnace, hot plate, or heating roller at a temperature of 100° C. to 300° C. (a temperature higher than the melting point of the crystalline resin). This allows the crystalline resin contained in the primer coat layer 3 to melt, and the bonding strength between the primer coat layer 3 and the conductor layer 2 or the bonding strength between the primer coat layer 3 and the electrode active material layer 5 to be reduced.
[0031] The peeling step may include a step of heating the primer coat layer 3 from the conductive layer 2 side. This can reduce the bonding strength between the primer coat layer 3 and the conductive layer 2. For example, the electrode 20 may be heated from the conductive layer 2 side with a hot plate, or the electrode 20 may be heated from the conductive layer 2 side with a heating roller. In addition, when the primer coat layer 3 and the electrode active material layer 5 are provided on both sides of the current collector 10, the primer coat layer 3 may be heated via the conductive layer 2 by heating a portion of the conductive layer 2 on which the primer coat layer 3 and the electrode active material layer 5 are not provided.
[0032] Fabrication of Lithium-ion Batteries Lithium ion batteries were produced in Examples 1 to 4 and Comparative Examples 1 to 4. Table 1 shows the amount of polyethylene (PE) contained in the primer coat layer of the positive electrode contained in each lithium ion battery and the mass (weight per unit area) of the primer coat layer. Table 1 also shows the amount of carbon particles contained in the primer coat layer of the positive electrode contained in each lithium ion battery in Examples 3 and 4 and Comparative Examples 2 to 4.
[0033] [Table 1]
[0034] [Example 1] A paint for the primer coat layer was prepared by mixing water and polyethylene particles (average particle size: about 10 μm). The mass (weight) of the primer coat layer per unit area was 6.4 g / m 2 The primer coat layer paint was applied to the corona discharge treated aluminum foil by gravure coating so that the primer coat layer was formed. The applied film was then dried to form a primer coat layer. In Example 1, the primer coat layer was formed using polyethylene particles, and it is believed that the primer coat layer is a layer in which polyethylene particles are scattered. A positive electrode active material, lithium nickel cobalt manganese oxide (ternary NCM811, average particle size 10 μm), a binder, and a solvent were mixed to prepare a positive electrode active material paste, which was then applied onto the primer coat layer and dried to form a positive electrode active material layer. In this manner, the battery positive electrode of Example 1 was produced.
[0035] A negative electrode active material paste was prepared by mixing graphite particles, which were a negative electrode active material, with an aqueous dispersion medium, and the negative electrode active material paste was applied onto a copper foil and dried to form a negative electrode active material layer. In this manner, a battery negative electrode was produced. A coin-type lithium ion battery of Example 1 was produced using the produced battery positive electrode, battery negative electrode, separator, and electrolyte.
[0036] [Example 2] In forming the primer coat layer, the mass (weight) of the primer coat layer per unit area is 1.0 g / m 2 The battery positive electrode and lithium ion battery of Example 2 were produced in the same manner as the battery positive electrode and lithium ion battery of Example 1, except that the primer coat layer paint was applied by gravure coating onto the corona discharge-treated aluminum foil so that the primer coat layer was formed using polyethylene particles. In Example 2, the primer coat layer is formed using polyethylene particles, and therefore the primer coat layer is considered to be a layer in which polyethylene particles are scattered.
[0037] [Example 3] The primer coat layer paint was prepared by mixing 100 parts by mass of polyethylene particles (average particle size: about 10 μm), 33 parts by mass of carbon particles (graphite particles + carbon black), and an aqueous dispersion medium, and the mass (weight) of the primer coat layer per unit area was 1.5 g / m 2 The battery positive electrode and lithium ion battery of Example 3 were produced in the same manner as the battery positive electrode and lithium ion battery of Example 1, except that the primer coat layer paint was applied by gravure coating onto the corona discharge-treated aluminum foil so that the primer coat layer was 0.01 to 0.01 mm thick. In Example 3, the primer coat layer was produced using polyethylene particles and carbon particles, and therefore the primer coat layer is considered to be a mixture layer of polyethylene particles and carbon particles.
[0038] [Example 4] The paint for the primer coat layer was prepared by mixing 100 parts by mass of polyethylene particles (average particle size: about 10 μm), 20 parts by mass of carbon particles (graphite particles + carbon black), and an aqueous dispersion medium, and the mass (weight) of the primer coat layer per unit area was 1.0 g / m 2The battery positive electrode and lithium ion battery of Example 4 were produced in the same manner as the battery positive electrode and lithium ion battery of Example 1, except that the primer coat layer paint was applied by gravure coating onto the corona discharge-treated aluminum foil so that the primer coat layer was formed from polyethylene particles and carbon particles. In Example 4, the primer coat layer was formed from polyethylene particles and carbon particles, and therefore the primer coat layer was considered to be a mixture layer of polyethylene particles and carbon particles.
[0039] [Comparative Example 1] In forming the primer coat layer, the mass (weight) of the primer coat layer per unit area is 10.0 g / m 2 The battery positive electrode and lithium ion battery of Comparative Example 1 were produced in the same manner as the battery positive electrode and lithium ion battery of Example 1, except that the primer coat layer paint was applied by gravure coating onto the corona discharge-treated aluminum foil so that the primer coat layer was 0.01 to 0.01 mm thick. In Comparative Example 1, the primer coat layer was produced using polyethylene particles, and therefore the primer coat layer is considered to be a layer of polyethylene particles. However, since the mass of the primer coat layer per unit area is large, the density of the polyethylene particles is considered to be high.
[0040] [Comparative Example 2] The primer coat layer paint was prepared by mixing 100 parts by mass of polyethylene particles (average particle size: about 10 μm), 50 parts by mass of carbon particles (graphite particles + carbon black), and an aqueous dispersion medium, and the mass (weight) of the primer coat layer per unit area was 0.4 g / m 2 The battery positive electrode and lithium ion battery of Comparative Example 2 were produced in the same manner as the battery positive electrode and lithium ion battery of Example 1, except that the primer coat layer paint was applied by gravure coating onto the corona discharge-treated aluminum foil so that the primer coat layer was formed from polyethylene particles and carbon particles. In Comparative Example 2, the primer coat layer was formed from polyethylene particles and carbon particles, and therefore the primer coat layer was considered to be a mixture layer of polyethylene particles and carbon particles.
[0041] [Comparative Example 3] The paint for the primer coat layer was prepared by mixing 100 parts by mass of polyethylene particles (average particle size: about 10 μm), 33 parts by mass of carbon particles (graphite particles + carbon black), and an aqueous dispersion medium, and the mass (weight) of the primer coat layer per unit area was 0.2 g / m 2 The battery positive electrode and lithium ion battery of Comparative Example 3 were produced in the same manner as the battery positive electrode and lithium ion battery of Example 1, except that the primer coat layer paint was applied by gravure coating onto the corona discharge-treated aluminum foil so that the primer coat layer was formed from polyethylene particles and carbon particles. In Comparative Example 3, the primer coat layer was formed from polyethylene particles and carbon particles, and therefore the primer coat layer was considered to be a mixture layer of polyethylene particles and carbon particles.
[0042] [Comparative Example 4] The primer coat layer paint was prepared by mixing 100 parts by mass of polyethylene particles (average particle size: approximately 10 μm), 20 parts by mass of carbon particles (graphite particles + carbon black), and an aqueous dispersion medium, and the mass (weight) of the primer coat layer per unit area was 10.5 g / m 2 The battery positive electrode and lithium ion battery of Comparative Example 4 were produced in the same manner as the battery positive electrode and lithium ion battery of Example 1, except that the primer coat layer paint was applied by gravure coating onto the corona discharge-treated aluminum foil so that the primer coat layer was formed from polyethylene particles and carbon particles. In Comparative Example 4, the primer coat layer was formed from polyethylene particles and carbon particles, and therefore the primer coat layer was considered to be a mixture layer of polyethylene particles and carbon particles.
[0043] Charge / discharge cycle test The lithium ion batteries of Examples 1 to 4 and Comparative Examples 1 to 4 were subjected to 100 charge / discharge cycles, and the charge / discharge cycle characteristics of each lithium ion battery were evaluated. The evaluation results are shown in Table 1. In Table 1, lithium ion batteries whose charge / discharge efficiency at the 100th cycle was 80% or higher are evaluated as "◯", and lithium ion batteries whose charge / discharge efficiency at the 100th cycle was 80% or lower are evaluated as "X". The lithium ion batteries of Examples 1 to 4 and Comparative Examples 2 and 3 were evaluated as "good," indicating that these batteries had high charge / discharge efficiency. The lithium ion battery of Comparative Example 1 was evaluated as "X". This is believed to be because the mass of the primer coating layer per unit area was large and the density of the polyethylene particles was high, resulting in high internal resistance of the positive electrode. The lithium ion battery of Comparative Example 4 was evaluated as "X." This is believed to be because the mass per unit area of the primer coat layer was increased, resulting in a high internal resistance of the positive electrode.
[0044] Peel test After 100 charge / discharge cycles, the lithium ion batteries of Examples 1 to 4 and Comparative Examples 1 to 4 were disassembled, the positive electrode was removed from the battery, and the electrolyte attached to the positive electrode was wiped off. Then, an adhesive tape was attached to a part of the positive electrode active material layer of the positive electrode, and a weight of 100 g was placed on the adhesive tape and moved back and forth three times to apply a load to the adhesive tape, so that the adhesive tape was firmly attached to the positive electrode active material layer. Then, the adhesive tape was peeled off from the aluminum foil. Then, the aluminum foil and the adhesive tape were observed to evaluate whether the positive electrode active material layer was peeled off from the aluminum foil (evaluation of "no heat treatment").
[0045] In addition, after 100 charge-discharge cycles, each positive electrode taken out from each lithium ion battery of Examples 1 to 4 and Comparative Examples 1 to 4 was heated on a hot plate at 200°C for about 5 seconds (heat treatment). After the heat treatment, an adhesive tape was attached to a part of the positive electrode active material layer of the positive electrode whose temperature had sufficiently decreased, and a weight of 100g was placed on the adhesive tape and moved back and forth three times to apply a load to the adhesive tape, so that the adhesive tape was firmly attached to the positive electrode active material layer. Then, the adhesive tape was peeled off from the aluminum foil. Then, the aluminum foil and the adhesive tape were observed to evaluate whether the positive electrode active material layer was peeled off from the aluminum foil (evaluation of "with heat treatment").
[0046] The evaluations for "without heat treatment" and "with heat treatment" are shown in Table 1. In Table 1, a positive electrode in which almost the entire positive electrode active material layer was peeled off from the aluminum foil together with the primer coat layer was evaluated as "◎", a positive electrode in which almost the entire positive electrode active material layer was separated from the primer coat layer and peeled off from the aluminum foil was evaluated as "◯", a positive electrode in which a part of the positive electrode active material layer remained on the aluminum foil was evaluated as "△", and a positive electrode in which almost the entire positive electrode active material layer remained on the aluminum foil was evaluated as "×".
[0047] The evaluation of the peel test of the positive electrodes of Examples 1 and 2 that were not subjected to heat treatment (evaluation without heat treatment) was "△", but the evaluation of the positive electrodes of Examples 1 and 2 that were subjected to heat treatment (evaluation with heat treatment) was "◯" or "◎". Therefore, it was found that in these positive electrodes, the positive electrode active material layer is easily peeled off from the aluminum foil by heat treatment. Therefore, it was found that the positive electrode has a primer coat layer in which polyethylene particles are scattered, and thus the positive electrode active material layer can be easily peeled off from the aluminum foil by heat treatment. The evaluation of the peel test of the positive electrodes of Examples 3 and 4 that were not subjected to heat treatment (evaluation without heat treatment) was "△", but the evaluation of the peel test of the positive electrodes of Examples 3 and 4 that were subjected to heat treatment (evaluation with heat treatment) was "◯". Therefore, it was found that in these positive electrodes, the positive electrode active material layer is easily peeled off from the aluminum foil by heat treatment. Therefore, it was found that the positive electrode has a primer coat layer that is a mixture layer of polyethylene and carbon particles, and therefore the positive electrode active material layer can be easily peeled off from the aluminum foil by heat treatment.
[0048] The peel test evaluation of the positive electrode of Comparative Example 1 that was not subjected to heat treatment (evaluation without heat treatment) was "◎", and the peel test evaluation of the positive electrode of Comparative Example 1 that was subjected to heat treatment (evaluation with heat treatment) was "◎". It is considered that the positive electrode of Comparative Example 1 received a high evaluation in the peel test because the density of the polyethylene particles in the primer coat layer was high. The evaluation of the peel test of the positive electrodes of Comparative Examples 2 and 3 that were not subjected to heat treatment (evaluation without heat treatment) and the evaluation of the positive electrodes of Comparative Examples 2 and 3 that were subjected to heat treatment (evaluation with heat treatment) were each "x". It is considered that the evaluation of the peel test was low in the positive electrodes of Comparative Examples 2 and 3 because the mass of the primer coating layer per unit area was small. The peel test evaluation of the positive electrode of Comparative Example 4 that was not subjected to heat treatment (evaluation without heat treatment) was "◯", and the peel test evaluation of the positive electrode of Comparative Example 4 that was subjected to heat treatment (evaluation with heat treatment) was "◎". It is considered that the positive electrode of Comparative Example 4 received a high evaluation in the peel test because the polyethylene content of the primer coat layer was high and the mass of the primer coat layer per unit area was large.
[0049] SEM observation The cut cross section of the positive electrode of Example 3 after the heat treatment was observed with an SEM. The SEM photograph is shown in FIG. 3. As can be seen from the photograph in FIG. 3, it was found that a gap was formed between the aluminum foil and the positive electrode active material layer. It is considered that the gap was formed by the polyethylene contained in the primer coat layer melting due to the heat treatment, causing the primer coat layer to peel off from the aluminum foil. In the positive electrodes of Examples 1 to 4 after the heat treatment, it is considered that the positive electrode active material layer became easily peeled off from the aluminum foil because such a gap was formed by the heat treatment. [Explanation of symbols]
[0050] 2: Conductive layer 3: Primer coat layer 4: Crystalline resin particles 5: Electrode active material layer 10: Battery current collector 20: Battery electrode
Claims
1. A conductive layer and a primer coat layer provided on the conductive layer, the primer coat layer is a layer of dispersed crystalline resin or a mixture layer of crystalline resin and carbon particles, When the primer coat layer is a layer of the dispersed crystalline resin, the conductive layer is exposed in gaps between the dispersed crystalline resin particles in the primer coat layer, When the primer coat layer is a mixture layer of a crystalline resin and carbon particles, the mass of the primer coat layer per unit area is 0.1 g / m 2 10g / m or more 2 Smaller, A current collector for a battery, wherein the melting point of the crystalline resin contained in the primer coat layer is 200° C. or lower.
2. 2. The battery current collector according to claim 1, wherein the primer coating layer is a mixture layer of a crystalline resin and carbon particles, and contains 0.01 parts by mass or more and 1,000 parts by mass or less of carbon particles per 100 parts by mass of the crystalline resin.
3. the primer coat layer is a layer of the dispersed crystalline resin, and is a layer in which crystalline resin particles having an average particle size D50 of 0.1 μm or more and 40 μm or less are dispersed; The mass of the primer coat layer per unit area is 0.1 g / m 2 More than 10 g / m 2 2. The battery current collector according to claim 1 .
4. the primer coat layer is a mixture layer of a crystalline resin and carbon particles, The size or thickness of the crystalline resin in the primer coat layer is 40 μm or less, The mass of the primer coat layer per unit area is 0.1 g / m 2 10g / m or more 2 2. The battery current collector according to claim 1, wherein:
5. 5. The battery current collector according to claim 4, wherein the primer coating layer is provided so that the carbon particles are not entirely coated with the crystalline resin.
6. The battery current collector according to claim 1 , wherein the conductive layer is a metal foil.
7. 2. The battery current collector according to claim 1, wherein the crystalline resin contained in the primer coat layer is a polyolefin.
8. 8. A battery electrode comprising the current collector according to claim 1 and an electrode active material layer provided on the primer coat layer.
9. A method for manufacturing a battery current collector, comprising the steps of applying a dispersion liquid in which crystalline resin particles are dispersed in a dispersion medium containing a water-soluble organic compound or a liquid organic compound and water onto a conductive layer, and drying the applied film to form a primer coat layer.
10. A method for peeling an electrode active material layer from a conductive layer, the electrode active material layer being included in an electrode comprising a current collector including a conductive layer and a primer coat layer provided on the conductive layer, and an electrode active material layer provided on the primer coat layer, the method comprising the steps of: the primer coat layer is a layer of dispersed crystalline resin or a mixture layer of crystalline resin and carbon particles, The melting point of the crystalline resin contained in the primer coat layer is 200° C. or less, The peeling method includes a peeling step of heating at least a part of the primer coat layer to a temperature equal to or higher than the melting point of the crystalline resin to peel off the electrode active material layer from the conductive layer.
11. 11. The method of claim 10, wherein the step of removing the electrode comprises heating the electrode with a furnace, a hot plate, or a heated roller at a temperature of 100° C. to 300° C. for a period of 0.5 seconds to 20 seconds.
Citation Information
Patent Citations
Electrode separation
JP2023511520A